Application of the project methods and information technologies in the study of the disciplines of mathematical, physical cycles of the higher school - I. I. Bobrova; E. G. Trofimov (Открытое образование (Москва))
When modeling various physical processes, the problem of the impossibility to predict the result in the changing conditions of the experiment was identified.The purpose of this work is to describe the methodology of projects with the use of information technology, which allows to “collect” different disciplines in the case and to form the applied profile skills described in the competencies to each of these disciplines. As an intensification of the educational process, the authors of the study see the use of automated computer tools in conjunction with other methodological techniques.Materials and methods. The basis of the methodological base of the study was the didactics’ materials, which can be attributed to the multidimensional principle (approach) of training, including the characteristics of different technologies, techniques and methods, such as:– technological principle (V. Bespalko, V. Guzeeva, T. Ilyina, E. Polat, G. Selevko, A. Uman and other scientists);– system-activity approach (V. Davydov, V. Slastenin, V.Monakhov, A. Kushnir, B. Skinner, S. Gibson, T. Sakamoto, and others);– procedural approach (M. Choshanov).During the development and implementation of our project the teaching methods are used: self-produce new knowledge based on existing ones; work in a team and demonstration of communicative skills; extension of educational hypotheses for solving problematic situations; planning the achievement of the goal (result); private methods of educational activity of students (detailing the tasks of the initial conditions and the progress of the experiment); the collection and processing of information, using computer programs.In fact, the method of projects combines search, research and information technologies, and the presence of an independent component in the process of learning and consolidation of knowledge is presented as a creative process. Methods of data analysis, systematization and visualization of the obtained data are used to understand and publish the results. Because of research, we have developed and tested a method of teaching students applying the knowledge gained in the study of different disciplines in the implementation of one interdisciplinary project.Results. The applied value of the study is that the described technique will allow future professionals to see the application of theoretical knowledge in practice; to acquire the skill of teamwork based on the strengths of each team member; to master the available software products that automate production and creative processes and to form the professional competence they need in the future.Conclusion. The described technique can be used both in a separate discipline (for example, “Equations of mathematical physics”) and as an interdisciplinary project that unites students in mastering the skills of not only one discipline, but also different specialties. The first results obtained by the authors in modeling the physical device (ozonizer) [1, p. 75–80], further work has been adjusted to reflect the new requirements of the educational process.